Efeitos de Avaliações Externas na Prática Profissional de Professores que Ensinam Matemática - Edivagner Souza dos Santos (2022)
The current work has as an aim to investigate the effects produced, and that are produced in effects, with external evaluations in the professional practice of teachers who teach Mathematics. Through a qualitative research approach, using the Semantic Fields Model and Oral History as theoretical and methodological foundations, interviews were carried out with seven teachers from the final years of Elementary School, who deal daily with external assessments. These historiographical movements gave rise to the textualizations of interviews, which produce a way in which each teacher reads the experienced scenario, is produced and crossed in it and, with these demands, builds political-economic-pedagogical strategies. These textualizations are constituted as writing-effects with external evaluations. Other writing-effects were produced, sometimes in dialogues with other researches on this theme, sometimes in movements of theorizations among tensions, anxieties, possibilities, demands and achievements of teachers who teach Mathematics in Elementary School. A decolonial attitude happens in between writings-effects, offering problematizations of ideas and everyday practices that happen in the school context with external evaluations. Each of the written-effects produced allows a look at a certain time-space-sense, which aims to problematize the existence of external evaluations. Effects of kidnapping of subjectivities of Mathematics teachers, effects of deletion, silencing, pressure and surveillance are produced throughout the writing. Effects of possible indicatives of external evaluations for propositions of political-economic-pedagogical strategies for Mathematics teachers, possibilities of spaces for discussions, problematizations and productions are also produced. Effects of external evaluations produced and that are produced can jeopardize schools as a rightful space for the entire population. They can be a strategy for the commodification of knowledge, as well as for the production of precarious human workers in countries with peripheral economies such as Brazil’s. Along with these discussions, the issue of external evaluations needs to be addressed. Keywords: External evaluation. Semantic Fields Model. Oral History. Decoloniality. Southern Epistemologies.